Principles and Practice of Blockchains - Daimi, Kevin; Dionysiou, Ioanna; El Madhoun, Nour. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book provides an essential compilation of relevant and cutting edge academic and industry work on key Blockchain topics. This book concentrates on a wide range of advances related to Blockchains which include, among others, Blockchain principles, architecture and concepts with emphasis on key and innovative theories, methodologies, schemes and technologies of Blockchain, Blockchain platforms and architecture, Blockchain protocols, sensors and devices for Blockchain, Blockchain foundations, and reliability analysis of Blockchain-based systems. Further, it provides a glimpse of future directions where cybersecurity applications are headed. The book is a rich collection of carefully selected and reviewed manuscripts written by diverse cybersecurity application experts in the listed fields and edited by prominent cybersecurity applications researchers and specialists.
Part I: Blockchain Fundamentals -- 1 Fundamentals of Blockchain Technology -- 2 Identification of Illicit Blockchain Transactions Using Hyperparameters Auto-tuning -- 3 Multidimensional Blockchain: Construction and Security Analysis -- 4 Blockchain Project Workflow Execution for Trustless Operations -- Part 2 Blockchains in Internet of Things and Mobile Phones -- 5 Protecting Location Privacy in Blockchain-based Mobile Internet of Things -- 6 A Blockchain Based Machine Learning Intrusion Detection System for Internet of Things -- 7 ECOM: Epoch Randomness-based Consensus Committee Configuration for IoT-Blockchains -- 8 Customer Outcome Framework for Blockchain-based Mobile Phone Applications -- Part 3 Blockchains and Healthcare -- 9 A Secure Decentralized Privacy-Preserving Healthcare System Using Blockchain -- 10 An Investigation of Blockchain Technology and Smart Contracts Deployment in Smart Medicine 4.0 -- Part 4 Blockchains and Currency -- 11 Post-Quantum Digital Signatures for Bitcoin -- 12 Cyber Laundering: Money Laundering from Fiat Money to Cryptocurrency -- Part 5 Blockchains in Education, Governance, Supply Chain, and Security -- 13 A Blockchain-based Fair and Transparent Homework Grading System for Online Education -- 14 Improving Supply Chain Management Performance with Blockchain Technology -- 15 Using Blockchain to Improve Corporate Governance -- 16 Blockchain Security as "People Security": Applying Sociotechnical Security to Blockchain Technology.
Keywords: Telecommunication; Computational intelligence; Data protection; Communications Engineering, Networks; Computational Intelligence; Data and Information Security